DYNAMICS OF FUTURE TEACHERS’ COGNITIVE READINESS DEVELOPMENT TO ORGANIZE STUDENTS’ DIALOGIC LEARNING - Fomin, Kateryna; Budnyk, Olena; Matsuk, Lyudmila; Mykhalchuk, Olena; Kuzenko, Оlexandra; Sirenko, Alla (Revista Inclusiones, 2020)
The results of the empirical research of forming teachers’ cognitive readiness to organize dialogic learning of students are described in the article. Methods of research: survey, pedagogical experiment (N = 294), methods of pedagogical statistics. The experiment revealed the level of cognitive readiness of future school teachers to organize a classroom dialogue. These indicators were analyzed in the control (CG) and experimental (EG) groups. Results: as a result of the experimental work the diagnostics of indicator formation of future primary school teachers’ cognitive readiness for the organization of dialogic learning has been carried out. A significant part of future teachers (according to the results of the ascertaining stage of the experiment) has been proved to be focused on directive and knowledge based learning and subject division of the content of education, do not always prefer innovations in terms of interactive and problem-based learning, have insufficient skills of organizing classroom educational dialogue. Having implemented our proposed educational model in vocational training a positive trend in the levels of cognitive readiness of future teachers to organize educational dialogue was observed. In particular, at the formative stage of the experiment we noticed the growth of the number of students with a high level of formation (39.7%, dynamics + 17.7%) of the cognitive component of professional readiness for the organization of dialogic learning in the EG. Statistically significant changes occurred mainly due to a decrease in the number of respondents who showed a low level of readiness for the experiment (31.7%, dynamics - 14.7%). In the control group, these changes are significantly smaller. Therefore, the methodological support of the process of primary school teachers’ training for the organization of dialogic learning is effective. It includes: dialogization of the content of pedagogical education, creation of an interactive educational environment for professional training; diversification of methods and forms of teaching in higher education, formation of educational student groups for constructive dialogue; development of critical thinking skills and pedagogical reflection